The effect of personality on occupational stress among employees in Universiti Teknologi MARA Perlis / Luqman Mahmud and Ahmad Nizan Mat Noor - Mahmud, Luqman; Mat Noor, Ahmad Nizan (Research Management Centre (RMC), 2023)
The education sector has significant well-being issues, with high levels of occupational stress and burnout. Previous research has focused on environmental factors in isolation, overlooking the influence of personality. Universiti Teknologi Mara Perlis (UiTM Perlis) (n=100) completed an online survey composed of three questionnaires; the NEO Five-Factor Inventory, the Maslach Burnout Inventory, and the Job Stress Survey. Multiple regression analysis revealed that personality is a better predictor of occupational stress than environment (p<.001). Neuroticism is the trait that significantly predicts occupational stress (p<.001), and the components of neuroticism that contribute the most to stress are depression (p=.002) and anger hostility (p=.005). Overall findings suggest that newly employees are at greater risk of suffering from high levels of occupational stress than those well established in the profession, and with higher levels of depression and anger hostility are likely to experience greater levels of occupational stress. Implications highlight the need for greater awareness of potentially susceptible personality traits in the employee's admissions process. This would allow for the identification of those at risk and the implementation of interventions.